Trade model with an optimal exchange rate motivated by current discussion of a Chinese Renminbi float - Hui Huang; Yi Wang; Yiming Wang; John Whalley; Shunming Zhang (Center for Economic Studies and ifo Institute (CESifo), 2005)
We combine a model of combined inter-spatial and inter-temporal trade between countries recently – used by Huang, Whalley and Zhang (2004) to analyze the merits of trade liberalization in services when goods trade is restricted – with a model of foreign exchange rationing due to Clarete and Whalley (1991) in which there is a fixed exchange rate with a surrender requirement for foreign exchange generated by exports. In this model, when services remain unliberalized there is an optimal trade intervention, even in the small open price-taking economy case. Given monetary policy and an endogenously determined premium value on foreign exchange, an optimal setting of the exchange rate can provide the optimal trade intervention. We suggest this model has relevance to the current situation in China where services remain unliberalized and tariff rates are bound in the WTO. Since there is an optimal exchange rate, a move to a free Renminbi float can be welfare worsening. We use numerical simulation methods to explore the properties of the model, since it has no closed form solution. Our analysis provides an intellectual counter argument to those presently advocating a free Renminbi float for China.
Keywords: F00; F4; F31; F11; 330; Internationaler Dienstleistungsverkehr; Aussenhandelsliberalisierung; Aussenwirtschaftstheorie; Zwei-Länder-Modell; Zeitökonomik; Allgemeines Gleichgewicht; Wohlfahrtseffekt; Theorie; Wechselkurs; Optimalzoll; Wechselkurssystem; China